Determinants of Disclosure of Carbon Emissions in Manufacturing Companies - ANNISA NABILAH HASAN (International Journal of Multidisciplinary Research and Studies, 2023)
This study examines the determinants of company size, leverage, industry type, and institutional ownership variables on the disclosure of carbon emissions. The quantitative research method is obtaining documentary data through annual reports and financial reports of manufacturing companies listed on the IDX for the 2017-2021 period. Sampling using purposive sampling with a total acquisition of 80 companies. Testing the research data using multiple regression analysis tests with SPSS 26 software. The study's results using multiple regression analysis tests show that company size, leverage, and industry type affect the disclosure of carbon emissions. Meanwhile, institutional ownership does not affect the disclosure of carbon emissions.